2015
DOI: 10.4197/med.22-3.5
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cell Alloimmunization in Sickle Cell Disease Patients in Jeddah, Saudi Arabia: A Pilot Study.

Abstract: The treatment of patients with sickle cell disease frequently requires transfusion of red blood cells. Complications due to alloimmunization of red blood cells antigen remain a major risk as a post transfusion effect. The objective of this study is to determine the frequency of red cell alloimmunization in Jeddah, Saudi Arabia. A retrospective cross-section study of sickle cell disease patients at King Abdulaziz University Hospital between 2012 and 2013 was performed. Demographic characteristics and transfusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…12 Rh and Kell blood group antibodies are most commonly expressed in both thalassemic and sickle cell patients, with other RBC antibodies also clinically implicated from reports. 16 Two recent studies on sickle cell and thalassemia patients at KAUH showed a high rate of alloimmunization: 61 out of 349 (17.47%) and 27 out of 134 (20.15%), respectively. These rates were shown to be higher in our study, which is due to frequent transfusions of non-phenotypically matched blood units.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…12 Rh and Kell blood group antibodies are most commonly expressed in both thalassemic and sickle cell patients, with other RBC antibodies also clinically implicated from reports. 16 Two recent studies on sickle cell and thalassemia patients at KAUH showed a high rate of alloimmunization: 61 out of 349 (17.47%) and 27 out of 134 (20.15%), respectively. These rates were shown to be higher in our study, which is due to frequent transfusions of non-phenotypically matched blood units.…”
Section: Discussionmentioning
confidence: 98%
“…3 Another study in the western part of the same country, carried out in 2012-2013 at KAUH, screened 234 sickle cell patients for alloantibodies, discovering that 12.8% (30 patients) expressed alloantibodies. 16 In a similar report from Oman, 31.5% (42/133) of sickle cell patients expressed alloantibodies. 21 The alloimmunization rates in this group of patients were also shown to greatly vary (18%-76%) in many other countries, including the United States, the United Kingdom, Kuwait, and Brazil.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…The frequency of alloimmunization depends on the heterogeneity of the donor-recipient population and the RBC administration matching process. Numerous studies have reported a wide frequency range of alloimmunization in thalassemia patients: 30% (57/190) in Kuwait, 4.97% (8/161) in India, 5% (72/1435) in Italy, 26.25 % (84/320) in Egypt, 22.06% (16/68) in Saudi Arabia and 3.7% (44/1200) in Greece [10][11][12][13][15][16][17][18][19][20][21] .…”
Section: Discussionmentioning
confidence: 99%